Menuju Industri Halal yang Berkeadilan: Integrasi Kesejahteraan Pekerja dalam Sistem Hukum Sertifikasi Halal di Indonesia - Tarmidzi, Tarmidzi; Inayati, Anindya Aryu; Tanzilullah, Muhammad Ilham; Saleh, Hairus; Humaida, Medina Janneta (Sharia Faculty Islamic Economic Law Study Department, 2026)
Despite the rapid growth of the halal sector globally in the food, cosmetics, pharmaceuticals, and finance sectors, the industry faces significant labor rights issues. This study aims to analyze how labor exploitation persists in the global halal supply chain and examines this issue through two lenses: Islamic law and international human rights. Using a normative legal research methodology, this study examines various cases of labor exploitation in the halal industry in Indonesia, Malaysia, the Middle East, and Brazil using both a comparative and contextual approach. The comparative study in Indonesia, Malaysia, and the halal industry in Asia reveals similar structural patterns, including persistent labor exploitation practices such as excessive working hours, precarious employment systems, and minimal social protection. This indicates that current halal certification regulations remain focused on halal compliance in production and have not yet integrated legal protection and worker welfare norms as essential components of halal standards. Such exploitation contradicts the Islamic legal principle of justice ('adl), and violates the values of al-kulliyyat al-khamsah in the maqāṣid al-shari'ah, particularly hifdz al-nafs and hifdz al-maal. From a human rights perspective, labor exploitation violates the global convention on decent work as stipulated in international labor standards established by the ILO and the UDHR. Ultimately, this paper proposes integrative reforms that guarantee labor welfare directly into halal certification standards, thereby ensuring the industry upholds Islamic integrity and universal human rights.